EMOJIS: VISUAL COMMUNICATION IN HIGHER EDUCATION - Doiron, J Gilles (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Emojis are increasingly becoming part of the lexicon many of our students recognize and use daily, and they are being touted as leading the way in the development of visual communication for sharing ideas and information. However, while research indicates that their use is helping to clarify or disambiguate messages, a number of issues have restricted their adoption in educational communication and feedback. To ensure that the intended connotation of an emoji is conveyed, companies that use emojis for branding and marketing, such as Pepsi, MTV, and Burger King, rely on custom-designed emojis their consumers can recognise and use in their text messages. Not only are these emojis used for selecting and ordering products and providing feedback on services, customers use them when communicating with their friends and family. To emulate the successful implementation of emojis in commerce, their use in higher education needs to be as targeted in purpose and meaning, and instructional designers need to define and develop a set of emojis specifically intended to support contemporary social-constructivist pedagogy. This paper looks at the current use of emojis in business and education and examines how a sound instructional design approach to the development of emojis could support learning through shared visual elements in contemporary social/educational media environments.